State of Vegetative and Humoral Regulations of Cardiac Rhythm in Young and Aged Rats on Background of Rhythmic Extreme Cooling (–120°C) Combined with Application of Cord Blood Nucleated Cells - Rudneva, Yuliya V.; Babiychuk, Vladislav G.; Chernyavskaya, Elena A.; Kulik, Vladimir V. (Problems of Cryobiology and Cryomedicine, 2013)
Spectral analysis of heart rate variability was used to study the state of vegetative and humoral regulations of heart rate in young and aged rats after combined use of rhythmic extreme cold exposures (RECE) and introduction of cord blood nucleated cells (CBNC). Thre was shown a positive effect of RECE and CBNC introduction on functional state of regulatory systems in organism of the animals regardless of age; that was confirmed by the rise of indices of total power spectrum of neurohumoral regulation due to activation of vegetative nervous system and humoral link of regulation. The findings testified that the process of heart rate control in aged animals after RECE and CBNC administration transited from a slow humoral-metabolic regulation level to a rapid vegetative level, not intrinsic to an aged organism.Probl Cryobiol Cryomed 2013; 23(4):318–325.